New insights into the roles of lactylation in cancer - Zhu, Yajun; Liu, Wenhui; Luo, Zhiying; Xiao, Feiyan; Sun, Bao (Frontiers in Pharmacology, 2024)
Lactylation, a novel discovered posttranslational modification, is a vital component of lactate function and is prevalent in a wide range of cells, interacting with both histone and nonhistone proteins. Recent studies have confirmed that lactylation as a new contributor to epigenetic landscape is involved in multiple pathological processes. Accumulating evidence reveals that lactylation exists in different pathophysiological states and leads to cancer, inflammation and cancerneuropsychiatric disorders; however, few mechanisms of lactylation have been elaborated. This review summarizes the biological processes and pathophysiological roles of lactylation in cancer, as well as discusses the relevant mechanisms and potential therapeutic targets, aiming to provide new insights for targeted cancer therapy.